The Knowledge of Contextual Factors as Triggers of Placebo and Nocebo Effects in Patients With Musculoskeletal Pain: Findings From a National Survey - Rossettini, Giacomo; Palese, Alvisa; Geri, Tommaso; Mirandola, Mattia; Tortella, Fabio; Testa, Marco (Frontiers in Psychiatry, 2019)
Backgrounds: Contextual factors (CFs) have been recently proposed as triggers of placebo and nocebo effects in musculoskeletal pain. CFs encompass the features of the: clinician (e.g. uniform), patient (e.g. expectations), patient-clinician relationship (e.g. verbal communication), treatment (e.g. overt therapy) and healthcare setting (e.g. design). To date, the researchers’ understanding of Italian patients’ knowledge about the role of CFs in musculoskeletal pain is lacking. Objectives: The aim of this study was to investigate attitudes and beliefs of Italian patients with musculoskeletal pain about the use of CFs in clinical practice. Methods: A national sample of Italian patients with musculoskeletal pain was recruited from 12 outpatients private clinics in Italy. An invitation to participate in an online survey was sent to patients: (a) exhibiting musculoskeletal pain; (b) aged 18-75; (c) with a valid e-mail account; and (d) understanding Italian language. Survey Monkey software was used to deliver the survey. The questionnaire was self-reported and it included 17 questions and 2 clinical vignettes on the patients’ behaviour, beliefs and attitudes towards the adoption of CFs in clinical practice. Descriptive statistics and frequencies described the actual number of respondents to each question. Results: 1112 patients participated in the survey. 574 participants were female (52%). The average age of patients was 41.7 ± 15.2 years. Patients defined CFs as an intervention with an unspecific effect (64.3%;), but they believed in their clinical effectiveness. They identified several therapeutic effects of CFs for different health problems. Their use was considered ethically acceptable when it exerts beneficial psychological effects (60.4%), but it was banned if considered deceptive (51.1%). During clinical practice patients wanted to be informed about the use of CFs (46.0%) that are accepted as an addition to other interventions to optimize clinical responses (39.3%). Moreover, patients explained the power of CFs through body-mind connections (37.1%). Conclusion: Patients with musculoskeletal pain had positive attitudes towards the use and effectiveness of CFs when associated with evidence-based therapy. They mostly perceived the adoption of CFs in clinical practice as ethical.